Relationship Between Educational Facilities and Classroom Management Quality in Early Childhood Education: Parents’ Perspectives at Al Hidayah Kindergarten, West Lombok - Yuliani, Yuliani; Suharyani, Suharyani; Hardiansyah, Rila; Herlina, Herlina; Sa'di, Kholisus (Reflection Journal, 2024)
The physical learning environment constitutes an important structural condition that may support classroom organization in early childhood education. This study examined the relationship between parents’ assessments of educational facilities and infrastructure and their assessments of classroom management quality at Al Hidayah Kindergarten, Bug-Bug Village, West Lombok, Indonesia. A quantitative correlational design was employed. The population consisted of 55 parents of enrolled children, of whom 25 were selected through purposive sampling based on their familiarity with the school environment and their children’s learning experiences. Data were collected using a 32-item five-point Likert questionnaire comprising 18 items on educational facilities and infrastructure and 14 items on classroom management. Reported item-total correlations ranged from .775 to .914, while the overall questionnaire yielded a Cronbach’s alpha of .945. Preliminary assumption testing produced a Shapiro-Wilk value of (W=.928), (p=.087), and no significant deviation from linearity, (F=.559), (p=.819). Simple linear regression revealed a strong positive and statistically significant association between parental ratings of educational facilities and classroom management, (R=.834), (R^2=.695), (F(1,23)=52.520), (B=.597), (SE=.082), (t(23)=7.247), (p<.001). Thus, within this sample, 69.5% of the variance in perceived classroom management quality was accounted for by variation in perceived educational facilities in the fitted model. Parents particularly valued safety, cleanliness, environmental maintenance, teacher friendliness, and time management. However, because both constructs were assessed by the same respondents, some indicators potentially overlapped conceptually, and the sample was small and nonprobabilistic, the findings should be interpreted as a strong association between two domains of parental perception rather than as evidence of a causal effect of facilities on classroom management.